2014
DOI: 10.1021/bi401263h
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Rescued Surface-Localized ΔF508 CFTR by Potentiation of Its Interaction with Na+/H+ Exchanger Regulatory Factor 1

Abstract: Cystic fibrosis (CF) is a recessive genetic disease caused by mutations in CFTR, a plasma-membrane-localized anion channel. The most common mutation in CFTR, deletion of phenylalanine at residue 508 (ΔF508), causes misfolding of CFTR resulting in little or no protein at the plasma membrane. The CFTR corrector VX-809 shows promise for treating CF patients homozygous for ΔF508. Here, we demonstrate the significance of protein–protein interactions in enhancing the stability of the ΔF508 CFTR mutant channel protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…Moreover, we asked whether small-molecule correctors might mediate the activation of ezrin and the inclusion of F508del CFTR in multiprotein complex to achieve their rescue of F508del CFTR functional expression. In this regard, it has been recently demonstrated that the known small-molecule corrector VX-809 enhances the stability and function on the cell surface of F508del CFTR (Eckford et al, 2014) and improves its interaction with NHERF1 (Arora et al, 2014;Loureiro et al, 2015). Indeed, we find here that both VX-809 ) and 4,6,4′-trimethylangelicin (TMA), a recently reported corrector and potentiator of F508del CFTR (Favia et al, 2014;Tamanini et al, 2011), involve both ezrin activation and actin cytoskeleton re-organization in their rescuing effect.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, we asked whether small-molecule correctors might mediate the activation of ezrin and the inclusion of F508del CFTR in multiprotein complex to achieve their rescue of F508del CFTR functional expression. In this regard, it has been recently demonstrated that the known small-molecule corrector VX-809 enhances the stability and function on the cell surface of F508del CFTR (Eckford et al, 2014) and improves its interaction with NHERF1 (Arora et al, 2014;Loureiro et al, 2015). Indeed, we find here that both VX-809 ) and 4,6,4′-trimethylangelicin (TMA), a recently reported corrector and potentiator of F508del CFTR (Favia et al, 2014;Tamanini et al, 2011), involve both ezrin activation and actin cytoskeleton re-organization in their rescuing effect.…”
Section: Introductionmentioning
confidence: 50%
“…In this regard, it has been recently demonstrated that one of the most promising correctors, VX-809 (Van Goor et al, 2011), stabilized F508del CFTR at the plasma membrane, improving its interaction with NHERF1 (Arora et al, 2014;Loureiro et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This closed structure of an enterosphere encompassing a central lumen allows investigators to study fluid dynamics (i.e., secretion and absorption) caused by physiological alterations in the epithelia that can result in either swelling or shrinkage of the enterospheres (22). It turned out that enterospheres are extremely useful models to study CFTR function in which forskolin, a cAMP agonist, induces rapid swelling of the enteropsheres, with normal CFTR caused by fluid filling the central lumen as CFTR becomes active (23)(24)(25). Loss-of-function CFTR mutants fail to stimulate secretion in such an assay as demonstrated by us and others (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…It turned out that enterospheres are extremely useful models to study CFTR function in which forskolin, a cAMP agonist, induces rapid swelling of the enteropsheres, with normal CFTR caused by fluid filling the central lumen as CFTR becomes active (23)(24)(25). Loss-of-function CFTR mutants fail to stimulate secretion in such an assay as demonstrated by us and others (23,24). We studied the effect of GCC activation on CFTR-dependent fluid secretion and found that incubation with STc stimulated swelling in the WT/WT Cftr enterospheres ( Figure 1, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…The localization of CFTR on the cell surface helps regulate clathrin and N-WASP-mediated endocytosis pathways, as well as Rab11-and Rme-1-mediated recycling pathways. The ΔF508-CFTR mutant is thought to have impaired interactions with NHERF1 and attenuated stabilization at the cell surface (43). We considered that expression of wild-type CFTR would result in stable cell surface CFTR and increased interactions of CFTR with scaffolding proteins that in turn inhibit C. jejuni invasion.…”
Section: Discussionmentioning
confidence: 99%